Influência da variação de rotação na otimização do custo energético de sistemas de bombeamento - Costa, José Nilton de Abreu (2019)
The operation of water supply systems almost always requires of hydraulic pumps, which allow the water to be conveyed to the final consumer. Drive fluids is a fundamental requirement in industries, in sanitation, in irrigation, and in several other areas using hydraulic pumps, spending on electricity. The energy costs associated with the operation of the pumps can be reduced through an alternative consisting of the use of rotating pumps (BRV) instead of fixed rotation pumps. BRV's are pumps coupled to a motor controlled by a frequency inverter whose function is to change the power supply to vary the speed of rotation of the pump in order to make it operate with the highest yield. In addition, other factors should be considered in the operation of a as possible combinations of operating rules, water demand, maintenance of reservoir levels and consumption within preset limits and also the efficient use of the energy tariff. In view of this scenario, this work was motivated operational conditions to the supply system in a rational manner, with an emphasis on optimization of the energy cost, through the creation of a computational model that acts of coupled to the EPANET hydraulic simulator. The tool developed in the process of metaheuristic technique known as PSO - Particle Swarm Optimization (Particle Swarm Optimization). speed of the pumps. This method is responsible for the search for strategies low energy costs, while performance evaluation of such strategies is carried out in EPANET. Another innovative proposition of this This thesis consists of the development of a new equation proposal, which allows the calculation of the final yield of a BRV when its speed is changed. The methodology This proposal was evaluated through three case studies. Through the results obtained, the effectiveness of the PSO was evidenced, as much by the meeting of better operational strategies as well as by the reduction of computational time required for such realization. Finally, It is considered that the development of this methodology can contribute to the use of optimization models in the operation of water supply systems in real time.